The effect of substrate-induced defects on structural and resistive switching properties in Gd0.2Ca0.8MnO3 thin films - Angervo, Ilari (American Institute of Physics, 2025)
Gd0.2Ca0.8MnO3 thin films were deposited on various substrate materials and their structural and resistive switching (RS) properties were investigated. The deposition resulted in epitaxial and polycrystalline films, with the latter also exhibiting distorted film surfaces. Both epitaxial and a part of polycrystalline films used as RS devices showed consistent RS performance in which an order of magnitude, or higher, switching ratios were achieved between high and low resistance states. The devices showed strong endurance during repeated switching cycles. However, under retention characterization, the resistance states did not remain distinguishable in devices constructed on polycrystalline films, while other devices maintained separable resistance states. The RS results are discussed in relation to the structural characteristics of the films, and this work helps us understand the RS mechanisms that still remain elusive in manganite-based devices.